The Physiological Basis of Improved Heat Tolerance in Selected Emmer-Derived Hexaploid Wheat Genotypes - Ullah, Smi; Trethowan, Richard; Bramley, Helen (Frontiers in Plant Science, 2021)
Wheat is sensitive to high-temperature stress with crop development significantly impaired depending on the severity and timing of stress. Various physiological mechanisms have been identified as selection targets for heat tolerance; however, the complex nature of the trait and high genotype × temperature interaction limits the selection process. A three-tiered phenotyping strategy was used to overcome this limitation by using wheat genotypes developed from the ancient domesticated wheat, emmer (Triticum dicoccon Schrank), which was considered to have a wide variation for abiotic stress tolerance. A contrasting pair of emmer-based hexaploid lines (classified as tolerant; G1 and susceptible; G2) developed from a backcross to the same recurrent hexaploid parent was chosen based on heat stress responses in the field and was evaluated under controlled glasshouse conditions. The same pair of contrasting genotypes was also subsequently exposed to a short period of elevated temperature (4 days) at anthesis under field conditions using in-field temperature-controlled chambers. The glasshouse and field-based heat chambers produced comparable results. G1 was consistently better adapted to both extended and short periods of heat stress through slow leaf senescence under heat stress, which extended the grain filling period, increased photosynthetic capacity, increased grain filling rates, and resulted in greater kernel weight and higher yield. The use of a combination of phenotyping methods was effective in identifying heat tolerant materials and the mechanisms involved.